Two Novel Variants in the ATRX Gene Associated with Variable Phenotypes. (6th November 2019) - Hettiarachchi, D.; Pathirana, B. A. P. S.; Kumarasiri, P. J.; Dissanayake, V. H. W.
Abstract : The X-linked alpha-thalassemia mental retardation (ATR-X) syndrome is a rare genetic condition caused by mutations in the X‐encoded gene ATRX . Here we describe two unrelated patients of Sri Lankan origin with novel missense variants in the ATRX gene: c.839C>T|p.Cys280Tyr and c.5369C>T|p.Ala1790Val. These two novel variants were associated with variable phenotypes which clinically resembled X-linked mental retardation-hypotonic facies syndrome and Smith-Fineman-Myers syndrome respectively. These cases expand the clinical spectrum of ATR-X syndrome and open new opportunities for the molecular diagnosis of ATRX mutations in male patients with severe global developmental delay and intellectual disabilities.